Kajian Konsep Green Infrastructure (Constructed Wetland) dalam Revitalisasi Kualitas Air di Kawasan DAS Cikapundung - Natasya Safira Viyanka Viyanka; Hilwati Hindersah (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. River is network of water from springs to estuaries which is bounded by a border line. The entry of waste into the river will cause changes in biological, chemical, and physical factors of the waters. Cikapundung watershed has a length of 28 km. The condition of the Cikapundung sub-watershed is currently experiencing a decline both quantitatively and qualitatively. Cikapundung River water pollution is caused by household waste, livestock waste and the rest is industrial waste. Management of water resources in the Cikapundung River is very important to prevent water pollution, further research is needed to discuss the revitalization of water quality in the Cikapundung River using the concept of green infrastructure (Constructed Wetland). The purpose of this study is to reduce water pollution in the Cikapundung watershed so that it can be reused according to its designation. The method used in this study is a mixed method of qualitative analysis and quantitative analysis. The results of this study are that the water pollution of the Cikapundung River is caused by human factors, the quality of the river water is quite polluted and highly polluted. The concept of green infrastructure (Constructed Wetland) is most appropriate to use in improving river water quality because it is able to effectively reduce river water pollutant levels. The total wastewater is 4,008,159,760 liters/day, so the need for artificial wetlands is 24 units with a capacity of 4,713,771,000 liters to accommodate wastewater from 7,856,286 people, with a volume of 166 m3/unit. Removal efficiency 9% - 88%. Abstrak. Sungai adalah suatu jaringan air dari mata air ke muara yang dibatasi oleh garis perbatasan. Masuknya limbah ke sungai akan menyebabkan perubahan faktor biologi, kimia, dan fisik perairan. DAS Cikapundung memiliki panjang 28 km. Kondisi sub-DAS Cikapundung saat ini mengalami penurunan baik secara kuantitatif maupun kualitatif. Pencemaran air Sungai Cikapundung disebabkan oleh limbah rumah tangga, limbah ternak dan sisanya limbah industri. Pengelolaan sumber daya air di Sungai Cikapundung sangat penting untuk mencegah pencemaran air, diperlukan penelitian lebih lanjut untuk membahas revitalisasi kualitas air di Sungai Cikapundung dengan menggunakan konsep infrastruktur hijau (Constructed Wetland). Tujuan dari penelitian ini untuk mengurangi pencemaran air di DAS Cikapundung sehingga dapat digunakan kembali sesuai dengan peruntukannya. Metode yang digunakan dalam penelitian ini adalah menggunakan Metode Campuran analisis kualitatif dan analisis kuantitatif. Hasil penelitian ini pencemaran air Sungai Cikapundung disebabkan oleh faktor manusia, memiliki kualitas air sungai yang cukup tercemar dan sangat tercemar. Konsep infrastruktur hijau (Constructed Wetland) paling tepat digunakan dalam meningkatkan kualitas air sungai karena mampu menurunkan kadar polutan air sungai secara efektif. Total air limbah adalah 4.008.159.760 liter/hari, sehingga kebutuhan lahan basah buatan sebanyak 24 unit dengan kapasitas 4.713.771.000 liter untuk menampung air limbah dari 7.856.286 orang, dengan volume 166 m3/unit. Efisiensi penghapusan kadar polutan 9% - 88%.